Modalities in Political Contestation: A Study of Nalladia Ayu Rokan's Victory in the 2024 Riau Legislative Election - Mayasari, Try; Situmorang, Tony P; Ridho, Hatta (Universitas Medan Area, 2025)
The 2024 general election will be held simultaneously to elect the president and vice president and to elect legislative members at the Regency/City and Provincial levels. In participating in political contestation, legislative candidates must have the modality as the main capital in participating in the election. This study uses a descriptive qualitative method by collecting primary data through interviews, observations, and documentation. The results of the survey show that Nalladia Ayu Rokan has an accumulation of three capitals, namely political capital that is superior to other legislative candidates, with the political position of her father, who is the leader of the Regional Head of Rokan Hilir Regency, can mobilize voters in obtaining votes, as well as support from political parties and successful teams that work structurally among the community. Furthermore, social modalities by conducting social interactions, communicating directly with the community to form trust in the community, as well as economic capital, namely campaign funds derived from personal wealth and party cash funds to carry out cost politics in gaining support from the community.